Rapid Differentiation of Chondroitin Sulfate Isomers by Gas-phase Hydrogen-deuterium Exchange - Alonge, Kimberly M.; Harkewicz, Rick; Guttman, Miklos (Current Molecular Medicine, 2020)
Chondroitin sulfate (CS)-glycosaminoglycans (GAGs) are linear, negatively charged polysaccharides attached to CS proteoglycans that make up a major component of biological matrices throughout both central and peripheral tissues. The position of their attached sulfate groups to the CS disaccharide is predicted to influence protein-glycan interactions and biological function. Although traditional immunohistochemical analysis of CS-GAGs in biological tissues has provided information regarding changes in GAG abundance during developmental and disease states, quantitative analysis of their specific sulfation patterns is limited due to the inherent complexity of separating CS isomers. While methods have been developed to analyze and quantify sulfation isomers using liquid phase separation, new techniques are still needed to elucidate the full biology of CS-GAGs. Here, we examine ion mobility spectrometry and gas-phase hydrogen-deuterium exchange to resolve positional sulfation isomers in the most common sulfated 4S- and 6S-CS disaccharides. The mobilities for these two isomers are highly similar and could not be resolved effectively with any drift gas tested. In contrast, gas-phase hydrogen-deuterium exchange showed very different rates of deuterium uptake with several deuterium exchange reagents, thereby presenting a promising novel and rapid approach for resolving CS isomers.
Keywords: deuterium